THE EFFECTIVENESS OF DIGITAL SERVICE POLICIES IN THE FORM OF ELECTRONIC SIGNATURES AT THE CIVIL POPULATION AND REGISTRY OFFICE IN SURABAYA CITY - Wulandari, Septiya; Sukristyanto, Agus; Novaria, Rachmawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Electronic signatures are one of the innovations in the improvement program of the Civil Registry and Population Office. Electronic signatures aim to streamline the process of verifying population documents without the need to visit in person and have face-to-face interactions. However, the community still questions the validity regarding the implementation of electronic signatures. The purpose of the study is to identify and analyze aspects that hinder and support, as well as to identify and analyze the Effectiveness of Digital Service Policies in the Form of Electronic Signatures at the Civil Registry and Population Office in Surabaya City. The research method used is descriptive qualitative with an inductive approach. Data collection techniques are carried out through interviews, observations, and documentation. In conducting interviews, the researcher analyzes the level of effectiveness using several indicators such as productivity level, flexibility level, effectiveness level, search for excellent human resources, job satisfaction of human resources, and supporting and inhibiting aspects. The research results indicate that digital services at the Civil Registry and Population Office, in the form of electronic signatures, have been implemented successfully. However, it still requires improvement in some obstacles, including several indicators, such as a lack of education and specific training for employees involved in the implementation of digital service policies, as well as a shortage of skilled human resources in handling network issues and unstable servers. Efforts made to overcome the existing obstacles include involving employees in training or technical guidance and repairing networks and servers experiencing disruptions. The researcher suggests the need for improvement in terms of education and specific training for employees involved in the implementation of digital service policies. Additionally, there is a need for dedicated human resources with a focus on network and server maintenance.